Genetic determinants of blood pressure traits are associated with carotid arterial thickening and plaque formation in patients with type 2 diabetes. (January 2019) - Engelbrechtsen, Line; Appel, Vincent E; Schnurr, Theresia M; Lundby-Christensen, Louise; Skaaby, Thea; Linneberg, Allan; Drivsholm, Thomas; Witte, Daniel R; Jorgensen, Marit E; Grarup, Niels; Pedersen, Oluf; Hansen, Torben; et al.
Objectives: The aim of this study is to explore the contribution of genetically driven cardiometabolic risk factors for development of carotid arterial thickening in patients with type 2 diabetes. Methods: In total, 12 genetic risk scores for blood pressure, blood lipids and glycaemic traits were constructed. The genetic risk scores were tested for association with carotid intima-media thickness and plaques in patients with type 2 diabetes ( n  = 401) and in non-diabetic individuals ( n  = 648) and for association with glucose levels in two population-based cohorts ( n  = 1328 and n  = 6161). Results: In patients with type 2 diabetes, the genetic risk scores for pulse pressure were positively associated with plaque formation ( β  = 0.036 ± 0.01 standard deviation/allele, p  = 0.003). The genetic risk score for diastolic blood pressure was negatively associated with carotid intima-media thickness ( β  = –0.037 ± 0.01 standard deviation/allele, p  = 0.005), although not significant after correction for multiple testing ( p  < 0.0042). In a meta-analysis of individuals with and without type 2 diabetes, the high-density lipoprotein genetic risk scores showed a trend towards an inverse association with carotid intima-media thickness and plaques, while the low-density lipoprotein genetic risk scores showed a trend towards a positive association with plaque formation but did reach the statistical threshold. Conclusion: Genetic loci for pulse pressure are associated with plaque formation among patients with type 2 diabetes, suggesting an underlying genetic contribution to arterial stiffening and atherosclerosis.